A Critical Evaluation of the WHO's Air Pollution Harm Reduction Strategy in Dhaka: Health Promotion, Behaviour Change, and Ethical Implications (Medicine Today, 2026)
Introduction: Air pollution is the causative factor for considerable morbidity and premature death worldwide. This review critiques the WHO's Air Pollution Harm Reduction Strategy in Dhaka, Bangladesh, through the lens of the HBM by analysing its effectiveness and ethical implications. Materials and Methods: This critical review synthesises findings from WHO publications, peer-reviewed journals, and public health data on Dhaka's air quality management. The approach involves thematic analysis of health promotion strategies and behavioural change interventions. Discussion: The findings highlight that while the WHO strategy is successful in raising awareness and providing a policy direction, it continues to be hampered by economic barriers, weak enforcement, and absence of local engagement. HBM explains personal motivation toward cleaner practices but falls short on systemic inequities and gendered exposures. Conclusion: A multi-sectoral policy enforcement, equity-focused planning, and culturally sensitive communication are some of the basic tenets for structuring Dhaka's air pollution strategy toward sustainable impact. Strengthening community ownership and data-driven governance bridges the gap between global frameworks and local realities.Medicine Today 2026, Vol.38 (1): 137-141